Karakteristik metastasis tulang belakang di Rumah Sakit Umum Pusat Sanglah - P. Gde Daniswara Raditya Rahman; Ni Putu Witari; Anak Agung Ayu Putri Laksmidewi; I Made Oka Adnyana (DiscoverSys Inc., 2021)
Introduction: Spinal metastases constitute 90% of spine tumors. Primary tumors originate from a variety of malignancies. However, there are no data on the characteristics of spinal metastases in the local population. This study collected data from one of the Tertiary hospitals in Bali to be used as a reference for the initial description regarding the characteristics of spinal metastases.Methods: A cross-sectional descriptive study was conducted by collecting medical record data of patients with spinal metastases at the Sanglah General Hospital for a year (January–December 2019) by total sampling.Results: This study obtained 39 samples. Most primary cancers that metastasize to the spine were lung cancers (30.77%), followed by multiple myeloma (10.26%), prostate cancer (7.69%), and colorectal cancer (5.13%). There were also contributions from breast, cervix, bladder, thyroid, lymphoma, nasal cavity, acute myeloid leukemia, and plasmacytoma. There were 25.64% cases where the primary cancer was unknown. Most of the metastases were in the thoracic segment (35.90%), followed by the lumbar region (28.21%) and the cervical region (12.82%). There were still many lesions that were less visible or unclear (38.46%). Patients generally experienced sensory (94.87%) and motor (92.31%) deficit. Sensory disturbances include paresthesia, hypesthesia and pain. Meanwhile, motor deficit include parapharesis, paraplegia, and tetrapharesis depending on the location of the lesion. Other disorders were related to the autonomic nerves (56.41%) such as defecation and urination problem.Conclusion: Most of the patients aged ?60 years and male. Spinal metastases frequently found in lung cancer patient. There was a high percentage cases with unknown primary origin. In general, the lesions were found in the thoracic and lumbar segments. There were many lesions which unclear or less visible in location. Almost all patients had sensory and motor deficit and only about half of patients had autonomic disorders. Pendahuluan: Metastasis tulang belakang merupakan 90% kasus tumor pada tulang belakang. Tumor primer dapat berasal dari berbagai keganasan. Akan tetap, belum ada data karakteristik metastasis tulang belakang di populasi lokal. Penelitian ini mengumpulkan data dari salah satu rumah sakit Tersier di Bali untuk dapat menjadi acuan gambaran awal terkait karakteristik metastasis tulang belakang.Metode: Penelitian deskriptif potong lintang dilakukan dengan mengumpulkan data rekam medis pasien dengan metastasis tulang belakang di Rumah Sakit Umum Pusat Sanglah selama satu tahun (bulan Januari - Desember 2019) secara total sampling.Hasil: Penelitian ini mendapatkan 39 sampel. Kanker primer terbanyak yang bermetastasis ke tulang belakang adalah kanker paru (30,77%), lalu disusul dengan multiple myeloma (10,26%), kanker prostat (7,69%), dan kanker kolorektal (5,13%). Terdapat pula kontribusi dari kanker payudara, serviks, buli, tiroid, limfoma, cavum nasi, leukemia myeloid akut, dan plasmasitoma. Terdapat 25,64% kasus tidak ditemukan lokasi kanker primernya. Lokasi metastasis paling banyak pada segmen thorakal (35,90%) kemudian regio lumbal (28,21%) dan regio servikal (12,82%). Masih banyak lesi yang kurang terlihat atau tidak jelas (38,46%). Pasien secara umum mengalami gangguan sensorik (94,87%) dan motorik (92,31%). Gangguan sensorik termasuk parestesia, hipestesia, dan rasa nyeri. Sedangkan gangguan motorik termasuk paraparesis, paraplegia, dan tetraparesis tergantung dari letak lesi. Gangguan lainnya yaitu gangguan pada saraf otonom (56,41%) dengan kelainan seperti gangguan buang air besar dan berkemih.Simpulan: Sebagian besar pada pasien usia ?60 tahun dan berjenis kelamin laki-laki. Metastasis tulang belakang cenderung lebih sering pada penderita kanker paru. Selain lokasi primer tersebut, terdapat persentase tinggi dimana tidak ditemukannya dari lokasi kanker primer. Pada umumnya hasil lesi terdapat pada segmen thorakal dan segmen lumbal. Masih banyak pula lesi ini masih kurang terlihat atau tidak jelas lokasinya. Pada umumnya pasien memiliki gangguan sensorik dan motorik serta hanya sekitar setengah pasien mengalami gangguan otonom.